Optimization in Feature Extraction schemes on Static Images to Improve the Performance of Automatic Facial Expression Recognition Systems - Naveen Kumar , HN; Jagadeesha , S; Jain, Amith K (International Journal of Computer Sciences and Engineering, 2019)
Automatic Facial Expression Recognition (AFER) systems are gaining importance in various emerging Human Computer Interaction (HCI) applications and affective computing applications. The abstract and robust features to interpret facial expressions and encode them as an emotion, still, remain as a challenge in the field of AFER. The objective of the proposed work is to analyze the performance of still image based AFER system with respect to various feature extraction schemes, and to optimize and thereby improving the recognition accuracy of AFER systems. Features such as; Histograms of Oriented Gradients (HOG), Local Binary Pattern (LBP) and a combination of HOG-LBP are used for the analysis of AFER system performance on feature extraction schemes. Various Parameters corresponding to features of interest are involved during the experimentation to understand the impact of a particular feature parameter on the recognition rate of AFER system. It’s not a simple task to optimize parameters of a feature to achieve better recognition rates. The proposed work is implemented on Extended Cohn-Kanade (CK+) dataset for six expressions. Cell size parameter of the features experimented has shown improvement in performance. Experimental results demonstrate the effectiveness of the proposed work on still image based facial expression recognition by providing significant performance improvement over other methods under comparison.